Green Energy: New Opportunities or Challenges to Energy Security for the Common Electricity Market of the Eurasian Economic Union Countries - Steblyakova, L.P.; Vechkinzova, E.; Khussainova, Zh.; Zhartay, Zh.; Gordeyeva, Y. (Energies, 2022)
The article discusses alternatives to the development of the common electricity market of the Eurasian Economic Union countries. In the study, the authors identified three tasks: to analyze the process of forming a unified energy market for the EAEU countries; to assess the achievability of indicators of “greening” the economy of the EAEU countries according to the adopted Millennium Goals by 2025 and 2030; and to consider the impact of various factors on the development of the common electricity market of the Eurasian Economic Union countries in the conditions of the current economic crisis. The research hypothesis suggests that the energy unification of the countries will not lead to the abandonment of the use of traditional energy resources, but the need to increase the efficiency and environmental friendliness of their use will come into focus, and the active inclusion of the electric power industry in modern global “green” trends based on the development of renewable energy generation sectors will make it possible to solve the problems of energy security of countries more effectively in the long-term participants of the CEM. The authors believe that it is not a deficit but on the contrary an excess of traditional energy resources that provides a trend of progressive movement towards a “green” economy, and the manifestations of the “Dutch disease” with a properly structured state energy policy and effectively selected incentive measures cannot serve as a significant brake on this movement. At the same time, the formation of a common electricity market of the EAEU countries should prioritize not just the idea of integration but also the idea of creating an alternative electricity market based on the introduction of modern electricity generation technologies and the creation of conditions that stimulate the development of alternative energy.
Keywords: common electricity market (CEM); green energy; renewable energy sources (RES); energy generation forecast; Eurasian Economic Union (EAEU)